Engineering an fgfr4 knockout zebrafish to study its role in development and disease. - Emma N Harrison; Amanda N Jay; Matthew R Kent; Talia P Sukienik; Collette A LaVigne; Genevieve C Kendall (PLoS ONE)
Fibroblast growth factor receptor 4 (FGFR4) has a role in many biological processes, including lipid metabolism, tissue repair, and vertebrate development. In recent years, FGFR4 overexpression and activating mutations have been associated with numerous adult and pediatric cancers. As such, FGFR4 presents an opportunity for therapeutic targeting which is being pursued in clinical trials. To understand the role of FGFR4 signaling in disease and development, we generated and characterized three alleles of fgfr4 knockout zebrafish strains using CRISPR/Cas9. To generate fgfr4 knockout crispants, we injected single-cell wildtype zebrafish embryos with fgfr4 targeting guide RNA and Cas9 proteins, identified adult founders, and outcrossed to wildtype zebrafish to create an F1 generation. The generated mutations introduce a stop codon within the second Ig-like domain of Fgfr4, resulting in a truncated 215, 223, or 228 amino acid Fgfr4 protein compared to 922 amino acids in the full-length protein. All mutant strains exhibited significantly decreased fgfr4 mRNA expression during development, providing evidence for successful knockout of fgfr4 in mutant zebrafish. We found that, consistent with other Fgfr4 knockout animal models, the fgfr4 mutant fish developed normally; however, homozygous fgfr4 mutant zebrafish were significantly smaller than wildtype fish at three months post fertilization. These fgfr4 knockout zebrafish lines are a valuable tool to study the role of FGFR4 in vertebrate development and its viability as a potential therapeutic target in pediatric and adult cancers, as well as other diseases.